The Oncogenic Role of microRNA-130a/301a/454 in Human Colorectal Cancer via Targeting Smad4 Expression - Lin Liu; Jing Nie; Lin Chen; Guanglong Dong; Xiaohui Du; Xin Wu; Yun Tang; Weidong Han (2013)
Transforming growth factor (TGF)-β/Smad signaling plays an important role in colon cancer development, progression and metastasis. In this study we demonstrated that the microRNA-130a/301a/454 family is up-regulated in colon cancer tissues compared to paired adjacent normal mucosa, which share the same 3′-untranslational region (3′-UTR) binding seed sequence and are predicated to target Smad4. In colorectal cancer HCT116 and SW480 cells, overexpression of miRNA-130a/301a/454 mimics enhances cell proliferation and migration, while inhibitors of these miRNAs affect cell survival. The biological function of miRNA-130a/301a/454 on colon cancer cells is likely mediated by suppression of Smad4, and the up-regulation of the miRNAs is correlated with Smad4 down-regulation in human colon cancers. Collectively, these results suggest that miRNA-130a/301a/454 are novel oncogenic miRNAs contributing to colon tumorigenesis by regulating TGF-β/Smad signaling, which may have potential application in cancer therapy.